Growth of Bacteria Bacillus cereus in Liquid Mediums with Different Carbohydrate Sources - Ningsih, Irma Ardila; Feliatra, Feli; Effendi, Irwan (Journal of Coastal and Ocean Sciences, 2020)
Bacteria need a medium to grow Bacillus cereus is a probiotic bacterium. Molasses and tofu liquid waste are one of the wastes that are used as alternative medium, because they are easy to obtain, cheap, and contain nutrients that are high enough in the form of carbohydrates. This study aimed to determine the optimal medium for the growth of these bacteria. This study used a completely randomized factorial design. It consists of three factors, namely the type of waste (molasses + egg albumen and tofu liquid waste + egg albumen), then the combination of isolates (B. cereus SN7 and consortium), and the concentration of liquid waste used for medium growth is (molasses is 1%; 1.5% ; and 2% while tofu liquid waste is 8%; 10%; and 12%). Bacterial cell growth was measured by the Total Plate Count (TPC) method, spectrophotometric method, and biomass, while the incubation period for cell growth was measured every 0, 6, 12, 18, and 24 hours. The results of this study indicated that molasses + egg albumen with a concentration of 1% was the best medium for the growth of B. cereus bacteria along with consortium isolates